Two new species of Agauopsis (Halacaridae, Acari) from Southeastern Brazil - Pepato, Almir R.; Tiago, Cláudio G. (Zootaxa, 2005)
Mites belonging to two new species of Agauopsis (Halacaridae, Acari) were obtained from seaweed, coarse sand and coarse shell debris taken from several sites in Northern Coast of São Paulo State. Agauopsis legionium sp. nov., which belongs to the brevipalpus group and Agauopsis itassussensis sp. nov., closely related to A. okinavensis Bartsch, 1986 are described.